Pendekatan Pendidikan Holistik: Mengembalikan Visi Pendidikan Berteraskan Kepercayaan dan Keyakinan Kepada Tuhan Melalui Proses Pengajaran dan Pembelajaran Bidang Teknikal dan Kejuruteraan (Sains Humanika, 2012)
Education is an effort to develop human potentials holistically. Therefore, education approach used in education process should be able to support this effort to develop holistic human being. Holistic approach is an alternative education approach in education. All this while, educator well exposed to education approach theory developed by Western scholar such as behaviorism, cognitive and constructive. These theories have been developed to address certain human potential but not spiritual potential. Therefore, holistic approach in education used to integrate spiritual knowledge (to address spiritual and emotion potential development) and intellectual knowledge (to address cognitive and psychomotor domain) based on one vision which is “to develop faith and devotion to God. In other words, the intellectual knowledge has become complementary to the spiritual knowledge to proof the greatness of Creator and to strenghten students’ belief in God existence. Therefore, the purpose of this study is to determine students’ perception towards the use of holistic approach in education by technical and engineering  lecturer. There are 133 final year students involved in this study. Quantitative research design has been used and a set of questionnaire has been developed. The reliability value for the questionnaire items was α=0.96. The finding indicates that the used of holistic approach in education by the lecturer is at moderate level. Therefore, there is a need to enhance the technical and engineering lecturer’s understanding and skill to use holistic approach in teaching and learning activities.
Keywords: Holistic; education approach; knowledge; integration